Monitoring diffuse volcanic degassing during volcanic unrests: the case of Campi Flegrei (Italy) - C. Cardellini (Nature Portfolio, 2017)
Abstract In volcanoes with active hydrothermal systems, diffuse CO2 degassing may constitute the primary mode of volcanic degassing. The monitoring of CO2 emissions can provide important clues in understanding the evolution of volcanic activity especially at calderas where the interpretation of unrest signals is often complex. Here, we report eighteen years of CO2 fluxes from the soil at Solfatara of Pozzuoli, located in the restless Campi Flegrei caldera. The entire dataset, one of the largest of diffuse CO2 degassing ever produced, is made available for the scientific community. We show that, from 2003 to 2016, the area releasing deep-sourced CO2 tripled its extent. This expansion was accompanied by an increase of the background CO2 flux, over most of the surveyed area (1.4 km2), with increased contributions from non-biogenic source. Concurrently, the amount of diffusively released CO2 increased up to values typical of persistently degassing active volcanoes (up to 3000 t d−1). These variations are consistent with the increase in the flux of magmatic fluids injected into the hydrothermal system, which cause pressure increase and, in turn, condensation within the vapor plume feeding the Solfatara emission.